2002
DOI: 10.1088/0953-2048/15/12/306
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy-stabilizedn-type superconducting cuprates

Abstract: We report the growth of n-type superconducting T′-(La,Ce)2CuO4 and infinite-layer (IL) (Sr,La)CuO2 thin films by means of molecular beam epitaxy (MBE). The bulk synthesis of T′-(La,Ce)2CuO4 and IL-(Sr,La)CuO2 requires complicated techniques: synthesis at low temperatures below 600 °C for the former and at high pressures above 3 GPa for the latter. This makes it difficult to grow bulk single crystals. We have found, however, that high-quality single-crystalline films of both compounds can be rather easily prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 22 publications
6
56
0
Order By: Relevance
“…Employing a thin film process, we also demonstrated that the superconducting range in T'-La 2-x Ce x CuO 4 is extended down to x = 0.045 [3], and also that the end-member T'-La 2 CuO 4 , which has been supposed to be a Mott insulator, shows metallic resistivity down to 150 K with ρ(300 K) as low as 2 mΩcm [4]. Furthermore, in the previous article, we reported the superconductivity with T c ~ 25 K in "undoped" T'-(La,RE) 2 CuO 4 , which was achieved by state-of-the-art molecular beam epitaxy (MBE) technique [5].…”
Section: Introductionmentioning
confidence: 80%
“…Employing a thin film process, we also demonstrated that the superconducting range in T'-La 2-x Ce x CuO 4 is extended down to x = 0.045 [3], and also that the end-member T'-La 2 CuO 4 , which has been supposed to be a Mott insulator, shows metallic resistivity down to 150 K with ρ(300 K) as low as 2 mΩcm [4]. Furthermore, in the previous article, we reported the superconductivity with T c ~ 25 K in "undoped" T'-(La,RE) 2 CuO 4 , which was achieved by state-of-the-art molecular beam epitaxy (MBE) technique [5].…”
Section: Introductionmentioning
confidence: 80%
“…In La 2-x Ce x CuO 4 , which can be stabilized by thin film synthesis [7], the superconducting region extend to lower doping (0.45 < x < 0.22) as compared with Pr 2-x Ce x CuO 4 and Nd 2-x Ce x CuO 4 . Although superconductivity does not appear at x = 0, the end-member T'-La 2 CuO 4 shows low resistivity (2 mΩcm at 300 K) and metallic behavior down to 150 K [8].…”
Section: Introductionmentioning
confidence: 99%
“…As seen in the figure, the T-phase films become more insulating with increasing x. The metallic behavior with a superconducting transition at about 30 K observed in the film with x = 0.09 is due to the impurity phase T'-La 2-x Ce x CuO 4 [6,7]. Figure 5 plots the resistivity at 300 K [ρ(300 K)] as a function of the Ce content.…”
Section: Methodsmentioning
confidence: 91%
“…The first concerns the inclusion of T'-La 2-x Ce x CuO 4 as an impurity phase. Because of the low synthesis temperature employed in MBE growth, the T' phase is easy to form and even predominates in preparation of La 2-x Ce x CuO 4 films for x even as small as 0.05 [6,7]. T'-La 2-x Ce x CuO 4 films are more conductive than T-La 2-x Ce x CuO 4 films by three to six orders of magnitude.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation